Social Justice in the Operation of the Medieval Crusader Knights’ Orders : On the Activities of the Polish Knights’ Orders - Małecki, Marian; Falus, Orsolya (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The charitable activities initiated by the monastic orders were continued by the some knights’ orders from the 11th century onwards, whose aim was to care for the sick and the poor. These were the hospitaller crusaders, whose roots grew out of the organization of hospitaller brotherhoods. Most of these formations reached Central and Eastern Europe, including Hungary and Poland. These special legal institutions represented divine justice in the conditions of the time: they protected the weak, spread the faith, and the hospitaller crusader orders performed an additional important, ‘public benefit’ task by caring for the sick in an era when institutionalized state frameworks for this activity did not yet exist. The aim of the paper is to – following in the footsteps of another study previously published in Díké, like a second part of it – present the functioning of such brotherhoods and knights’ orders in Poland in the 12th and 13th centuries, and to examine at what levels of activity these legal institutions can be seen to be engaged in social justice.